Captain Cat - Moore, Inga (Somerville, Massachusetts : Candlewick Press, 2013)
Loving cats so much that he has more feline than human companions on his ship, Captain Cat arrives on an island overrun by rats that his feline charges rapidly trounce, a triumph that results in an offer that requires a difficult decision.
Keywords: Cats -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Islands -- Juvenile fiction; Cats -- Fiction; Human-animal relationships -- Fiction; Islands -- Fiction